Highly sensitive avidin-biotin ELISA for detection of nandrolone and testosterone in dietary supplements - Jurášek, Michal; Göselová, Sandra; Mikšátková, Petra; Holubová, Barbora; Vyšatová, Eva; Kuchař, Martin; Fukal, Ladislav; Lapčík, Oldřich; Drašar, Pavel (Drug testing and analysis, 2017)
Avidin-biotin technology was used for the implementation of an enzyme-linked immunosorbent assay (AB-ELISA) as a sensitive method for the detection of anabolic androgenic steroids (AAS) present in dietary supplements. Using click chemistry, novel haptens (linker-optimized biotinylated nandrolone (NT) and testosterone (T) at positions C-3 and C-17, respectively) were designed and synthesized to be then applied as four different immobilized competitors in a proposed set of four indirect competitive AB-ELISAs. Four rabbit polyclonal antibodies of various specificities were prepared using four different immunogens synthesized from C-3 and C-17 carboxymethyloxime and hemisuccinate derivatives of NT and T, respectively. Assembled AB-ELISAs were characterized to establish method parameters such as a half-maximum inhibition concentration (0.18-12.99 ng/mL), limit of detection (0.004-0.032 ng/mL) and linear working range (the best with 0.02-1.38 ng/mL). The stability of the set simulating storage in different conditions was demonstrated. Cross reactivity (CR) was tested for 59 steroids including both endogenous and synthetic analogues in four assembled AB-systems. The focus was placed on the practical use of the method in detection of various AAS in 49 samples of counterfeit dietary supplements. The concordance between ultra high performance liquid chromatography-mass spectrometry (UHPLC-MS) and the CR corrected data from AB-ELISA indicated the potential of this method even to quantification of T propionate, NT phenyl propionate, and NT decanoate in such a complex matter. Copyright © 2016 John Wiley & Sons, Ltd.
Keywords: anabolics; nandrolon; avidin; anabolika; testosterone; potravní doplňky; Limit of Detection; Testosterone; limita detekce; Avidin; nandrolone; testosteron; dietary supplements; Biotin; ELISA; zvířata; Anabolic Agents; králíci; Dietary Supplements; Rabbits; Nandrolone; biotin; Enzyme-Linked Immunosorbent Assay; Animals